Digital heritage. progress in cultural heritage : documentation, preservation, and protection : 7th International Conference, EuroMed 2018, Nicosia, Cyprus, October 29-November 3, 2018, Proceedings /: progress in cultural heritage : documentation, preservation, and protection : 7th International Conference, EuroMed 2018, Nicosia, Cyprus, October 29-November 3, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available